Integrative genomics of gene and metabolic regulation by estrogen receptors α and β, and their coregulators. Issue 1 (18th June 2013) - Madak‐Erdogan, Zeynep; Charn, Tze‐Howe; Jiang, Yan; Liu, Edison T; Katzenellenbogen, John A; Katzenellenbogen, Benita S
Abstract : The closely related transcription factors (TFs), estrogen receptors ERα and ERβ, regulate divergent gene expression programs and proliferative outcomes in breast cancer. Utilizing breast cancer cells with ERα, ERβ, or both receptors as a model system to define the basis for differing response specification by related TFs, we show that these TFs and their key coregulators, SRC3 and RIP140, generate overlapping as well as unique chromatin‐binding and transcription‐regulating modules. Cistrome and transcriptome analyses and the use of clustering algorithms delineated 11 clusters representing different chromatin‐bound receptor and coregulator assemblies that could be functionally associated through enrichment analysis with distinct patterns of gene regulation and preferential coregulator usage, RIP140 with ERβ and SRC3 with ERα. The receptors modified each other's transcriptional effect, and ERβ countered the proliferative drive of ERα through several novel mechanisms associated with specific binding‐site clusters. Our findings delineate distinct TF‐coregulator assemblies that function as control nodes, specifying precise patterns of gene regulation, proliferation, and metabolism, as exemplified by two of the most important nuclear hormone receptors in human breast cancer. Abstract : To define how the estrogen receptors α and β control specific responses in breast cancer cells, genome‐wide patterns of chromatin binding of the ERα and ERβ receptors and their coregulators, SRC3 and RIP140, were determined and integrated with gene expression data and functional analyses. Synopsis: To define how the estrogen receptors α and β control specific responses in breast cancer cells, genome‐wide patterns of chromatin binding of the ERα and ERβ receptors and their coregulators, SRC3 and RIP140, were determined and integrated with gene expression data and functional analyses. The closely related transcription factors, estrogen receptors ERα and ERβ, can elicit differential cellular responses. To understand the basis of this specificity, chromatin binding of ERs and key coregulators, and gene expression, were analyzed genome wide in human breast cancer cells containing ERα only, ERα+ERβ, and ERβ only. A clustering‐based combinatorial analysis of ChIP‐Seq and gene expression data was used to parse genes into groups, specifying their mode of functional regulation in a particular cell background. Through this analysis, RIP140 was identified as an ERβ‐preferential cofactor regulating cell proliferation, apoptosis, and adipogenesis programs. A 20‐gene ERβ and RIP140 signature was developed, which predicted outcome and disease‐free survival in breast cancer patients.